2008
DOI: 10.1097/brs.0b013e318186b258
|View full text |Cite
|
Sign up to set email alerts
|

Total Disc Replacement Positioning Affects Facet Contact Forces and Vertebral Body Strains

Abstract: The current study predicted a decrease in segmental rotational stiffness resulting from TDR. This resulted from the removal of load bearing soft tissue structures, and caused increased loading in the facets. Additionally, vertebral body strains were generally higher after TDR, and tended to increase with decreased rotational stiffness. Posterior placement of the device provided a more physiologic load transfer to the vertebral body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 61 publications
3
57
1
Order By: Relevance
“…Ahn et al [267] also incorporated different disc designs in their C5-C6 model and reported that facet loads increase when the center of rotation of the spherical joint of the implant is constrained. Additional studies find that the antero-posterior placement of an artificial disc also affects the flexural stiffness of the motion segment at the level of the implant and the loads transferred to the facet during all modes of loading [264,266,268,274]. In general, all of these studies have found that a posterior position of a disc implant can unload the facets although the influence of this parameter should be considered in conjunction with the influence of other parameters such as the implant design, anatomical modeling, and constitutive equations employed in the individual finite element models.…”
Section: Models Simulating Clinicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahn et al [267] also incorporated different disc designs in their C5-C6 model and reported that facet loads increase when the center of rotation of the spherical joint of the implant is constrained. Additional studies find that the antero-posterior placement of an artificial disc also affects the flexural stiffness of the motion segment at the level of the implant and the loads transferred to the facet during all modes of loading [264,266,268,274]. In general, all of these studies have found that a posterior position of a disc implant can unload the facets although the influence of this parameter should be considered in conjunction with the influence of other parameters such as the implant design, anatomical modeling, and constitutive equations employed in the individual finite element models.…”
Section: Models Simulating Clinicalmentioning
confidence: 99%
“…Mathematical and finite element models offer great utility for investigating spinal tissue responses because they provide an alternative to experimental approaches that can present a wide variety of challenges owing to a scarcity of specimens and a potential poor tissue quality due to advanced age or degeneration. In addition, mathematical models enable an infinite number of model conditions and variations that can be set up to investigate the influence of biological and mechanical conditions that alter tissue properties [310,311], or to compare effects of surgical procedures such as laminectomy, facetectomy, or disc arthroplasty [264][265][266]274,[312][313][314] on the mechanical behavior of the spine. Computational approaches can extend beyond experiments that can be limited in their utility if restricted to cadaveric tissue only.…”
Section: Mathematical and Finite Element Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To implant disc prosthesis, resection of both anterior longitudinal ligament (ALL) and anterior annulus is required. As a direct result of loss of these structures, a significant increases in range of axial rotation and facet loading would occurred [23,24], and a motion segment where disc prosthesis was implanted became vulnerable to rotatory instability. By nature, the role of facet joint is to limit the axial rotation and maintain the stability of motion segment [25], however, with asymmetry of facet joint, uneven rotatory movement would occur [10] and that would be more worsened by absence of ALL and anterior annulus after prosthesis implantation and accordingly, accelerate or give birth to the development of PFA after TDR.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the TDR also appears to influence the loading that occurs at the facets [23]. Finally, placement and the height of the TDR appear to be important considerations for biomechanical function [27][28][29].…”
Section: Introductionmentioning
confidence: 99%